Age-Related Macular Degeneration: What Do We Know So Far? - Ma, Ho Hin; Liutkevičienė, Rasa (Acta medica Lituanica, 2021)
Ageing is a natural process that everyone experiences and nobody is an exception. With ageing, our body experiences physiological changes. In this article, the focus is made on the physiological changes of our eyes related to ageing and age-related macular degeneration (AMD), which is the most common cause of incurable visual impairment in developed countries. With ageing populations increasing in many countries, more and more patients will have AMD in a foreseeable future. In Eastern Europe, blindness due to AMD, currently, is approximately 20% and there has been an increasing trend depicted in the future. Generally, AMD can be divided into early stages and two forms in an advanced (late) stage. Advanced AMD form includes neovascular AMD (wet) and geographic atrophy (late dry), both of these are associated with substantial, progressive visual impairment. The pathogenesis of AMD is complex and, by far, not completely understood. Multiple factors have been studied, for example: environmental factor, genetic factor (complement factor H), lifestyle. It has been proved that they are linked to higher the risk of developing of AMD, however, the actual pathogenesis is not yet formulated. AMD progression can also be a culprit to certain biochemical events and molecular changes linked to inflammation and pathological angiogenesis. In nowadays, we do have diagnostic methods for both early and late forms of AMD as well as ways to prevent progression of early AMD and wet AMD. However, until now, there is still no treatment for dry AMD. This article is a brief review of AMD and may hopefully lead to some future directions in early diagnostic methods and treating dry AMD.